Rationales of employees' perception on private colleges' internal reputation: a case study of ABC College - Abu Seman, Rabiatul Adawiyah; Abdullah, Zulhamri (2012)
High turnovers and commitments in private colleges are affiliated with organisation's internal reputation. This study focused on importance and strength of the internal reputation drivers and how employees‟ perceptions on internal reputation influence their behaviour or commitment towards their employer. Data collected was administered using Pearson Correlation and Regression based on questionnaire built from WorkRep model. This study indicated drivers‟ relationship strength to internal reputation from strongest to moderate as followed: (1) leadership and performance (2) products and responsibility (3) work environment (4) total rewards and (5) work environment. Biggest factor contributing to internal reputation is leadership and performance unlike work environment does the other way round. There was also significantly strong relationship between internal reputation and employees' supportive behaviour. This study provided insights of the important areas in strategic reputation management of private colleges. Smart reputation management results in a strong corporate reputation as it influences employees' behaviour towards other important stakeholders such as students and customers. As the most important people in an organisation, leaders can control all reputation drivers and shape individual's perception generally. Thus, extensive qualitative research on internal reputation or on leadership's role in shaping internal reputation would give deeper insights of internal reputation.